The effect of different neural mobilization exercises on hamstring flexibility and functional flexibility in wrestlers - Balci, A.; Ünüvar, E.; Akinoglu, B.; Kocahan, T. (Journal of Exercise Rehabilitation, 2020)
This study aimed to compare the short-term effects of sciatic nerve neural sliding and neural stretching exercises on hamstring muscle length and functional flexibility in wrestlers. The study participants included 74 wrestlers. The athletes were randomly divided into two groups: neural sliding and neural stretching groups. The hamstring flexibility and the functional flexibility were assessed using the active knee extension limitation (AKEL) angle and the sit and reach (SR) test one day before and immediately after the neural mobilization exercises, respectively. A three-way repeated measures analysis of variance was conducted that examined the effect of mobilization type, time, and gender on interest in AKEL right leg, AKEL left leg, and SR test. There is not a significant difference between the effect of two different mobilizations on AKEL right and left leg, and SR test (P>0.05). It was determined there is statistically significant differences between premobilization and post-mobilization outcome measures for AKEL right leg (F=59.886, P=0.001), AKEL left leg (F=31.896, P=0.001), and SR test (F=22.630, P=0.001). There is not a statistically significant difference between males and females by these three measures neural sliding and neural stretching exercises to the sciatic nerve in wrestlers were effective in increasing hamstring flexibility and functional flexibility and not superior to each other.